Evaluation of Population Indices and Estimators for Scaled Quail in the Rolling Plains of Texas - Bradley Kubečka; John T. Edwards; Fidel Hernández; Dale Rollins (National Quail Symposium Proceedings, 2017)
Accurate and precise population indices and estimators are important to gain reliable knowledge and make appropriate management decisions. Indices and estimators for scaled quail (Callipepla squamata), however, have not been evaluated thoroughly. Our objectives are to compare relationships among 8 years of roadside counts, spring call counts, and mark-recapture data obtained from the Rolling Plains Quail Research Ranch in Fisher County, TX, USA. Furthermore, we assess the efficacy of distance-based helicopter surveys as a method for scaled quail density estimates as compared to mark-recapture estimates for 2016–2017.
Keywords: scaled quail; callipepla squamata; population indices; mark-recapture; density estimates